Synthesis of N-arylindazole-3-carboxamide and N-benzoylindazole derivatives and their evaluation against α-MSH-stimulated melanogenesis. Issue 18 (15th September 2019) - Arepalli, Sateesh Kumar; Lee, Chaerim; Jung, Jae-Kyung; Kim, Youngsoo; Lee, Kiho; Lee, Heesoon
Graphical abstract: Highlights: Twenty-six indazole analogs were designed, synthesized and evaluated as α-MSH inhibitors. Eighteen compounds exhibited more potent inhibition than reference arbutin. The compound (3k ) displayed 5 times more α-MSH inhibition than arbutin. The compound (6g ) displayed 9 times more α-MSH inhibition than arbutin. Structure-activity relationship was developed. Abstract: We have designed and synthesized twenty-six N -arylindazole-3-carboxamide (3a-p ) and N -benzoylindazole (6a-j ) derivatives to discover with excellent inhibition activities of α-MSH-stimulated melanogenesis. In the bio evaluation studies of these compounds, we discovered eighteen compounds, out of twenty-six exhibited more potent inhibition than the positive control arbutin. From the SAR studies, we identified 3k and 6g as lead compounds which displayed almost 5 and 9 times more potent inhibition of α-MSH-stimulated melanogenesis respectively than the reference arbutin. It is also evident the presence of electron withdrawing group at para position (R 3 ) for the compounds (3a-p ) and presence of +M group at ortho position (R 5 ) for the compounds (6a-j ) were crucial for their excellent inhibition activities of α-MSH-stimulated melanogenesis.